Loss of expression of protein phosphatase magnesium‐dependent 1A during kidney injury promotes fibrotic maladaptive repair. Issue 10 (21st June 2016) - Samarakoon, Rohan; Rehfuss, Alexandra; Khakoo, Nidah S.; Falke, Lucas L.; Dobberfuhl, Amy D.; Helo, Sevann; Overstreet, Jessica M.; Goldschmeding, Roel; Higgins, Paul J.
ABSTRACT: Protein phosphatase magnesium‐dependent‐1A (PPM1A) dephosphorylates SMAD2/3, which suppresses TGF‐β signaling in keratinocytes and during Xenopus development; however, potential involvement of PPM1A in chronic kidney disease is unknown. PPM1A expression was dramatically decreased in the tubulointerstitium in obstructive and aristolochic acid nephropathy, which correlates with progression of fibrotic disease. Stable silencing of PPM1A in human kidney‐2 human renal epithelial cells increased SMAD3 phosphorylation, stimulated expression of fibrotic genes, induced dedifferentiation, and orchestrated epithelial cell‐cycle arrest via SMAD3‐mediated connective tissue growth factor and plasminogen activator inhibitor‐1 up‐regulation. PPM1A stable suppression in normal rat kidney‐49 renal fibroblasts, in contrast, promoted a SMAD3dependent connective tissue growth factor and plasminogen activator inhibitor‐1–induced proliferative response. Paracrine factors secreted by PPM1A‐depleted epithelial cells augmented fibroblast proliferation (>50%) compared with controls. PPM1A suppression in renal cells further enhanced TGF‐b1–induced SMAD3 phosphorylation and fibrotic gene expression, whereas PPM1A overexpression inhibited both responses. Moreover, phosphate tensin homolog on chromosome 10 depletion in human kidney‐2 cells resulted in loss of expression and decreased nuclear levels of PPM1A, which enhanced SMAD3‐mediated fibrotic gene induction and growth arrest that were reversed by ectopic PPM1A expression. Thus, phosphate tensin homolog on chromosome 10 is an upstream regulator of renal PPM1A deregulation. These findings establish PPM1A as a novel repressor of the SMAD3 pathway in renal fibrosis and as a new therapeutic target in patients with chronic kidney disease.—Samarakoon, R., Rehfuss, A., Khakoo, N.S., Falke, L. L., Dobberfuhl, A.D., Helo, S., Overstreet, J.M., Goldschmeding, R., Higgins, P. J. Loss of expression of protein phosphatase magnesium‐dependent 1A during kidney injury promotes fibrotic maladaptive repair. FASEBJ. 30, 3308–3320 (2016). www.fasebj.org